Property Purchase: Issues and Challenges Facing by First House Buyers in Malaysia During Covid-19 Pandemic (Year 2020-2022) - Khoo, Terh Jing; Hoo, Vicky Ying Qi; Yee, Ha Chin (UUM PRESS, 2024)
This article intended to identify issues and challenges facing by first house buyers when they are buying first house in Malaysia. The results from this article can provide insights to related stakeholders in helping first house buyers to come up with better policies. With the development of the economy, housing prices are still unaffordable and are gradually rising every year. However, household income has not increased accordingly, which is the main problem affecting Malaysians’ difficulty in affording a house. Previously the Malaysian homeownership rate is already declining due to the expensive house price where the COVID-19 pandemic has caused a severe downturn2 Jurnal Pembangunan Sosial, Vol. 27 (July) 2024, pp: 1–24 to Malaysia, especially the housing market which has been affected poorly. This article adopted quantitative research method where the primary data was collected through questionnaire surveys. The sample size was determined by referring to Krejcie and Morgan method. The questionnaires are distributed through internet platforms such as Facebook, Instagram, and WhatsApp to collect more responses as online survey brings convenience to respondents. 155 responds were collected from the respondents. From the results, unstable financial positions, unemployment rate, difficulty in obtaining loans, and location factors are the first house buyers’ main issues and challenges. These factors required intervention from the government to save the economy through several policies. Since majority of first house buyers are not familiar with the issues and challenges that they need to consider before making the decision to purchase their first house, this article’s outcomes help first house buyers to do decisions by discussing the issues and challenges that need to be considered. Furthermore, the outcomes can be referred to once the first house buyers encounter similar situations as the results can be used as guidance to help them to understand the problems.